META‐ANALYSIS OF ECONOMICS RESEARCH REPORTING GUIDELINES. (6th March 2013) - Stanley, T.D.; Doucouliagos, Hristos; Giles, Margaret; Heckemeyer, Jost H.; Johnston, Robert J.; Laroche, Patrice; Nelson, Jon P.; Paldam, Martin; Poot, Jacques; Pugh, Geoff; Rosenberger, Randall S.; Rost, Katja
Abstract: Meta‐regression analysis (MRA) can provide objective and comprehensive summaries of economics research. Their use has grown rapidly over the last few decades. To improve transparency and to raise the quality of MRA, the meta‐analysis of economics research‐network (MAER‐Net) has created the below reporting guidelines. Future meta‐analyses in economics will be expected to follow these guidelines or give valid reasons why a meta‐analysis must deviate from them.